Time Travel as Homecoming A Journey for Eternity and a Day(Theo Angelopoulos, GR 1998) - Wu, Haotian (Journal for Religion, Film and Media)
Time is an essential issue in phenomenology and existential philosophy. In this article, I argue that Μια αιωνιότητα και μια μέρα (Eternity and a Day, Theo Angelopoulos, GR 1998), the masterpiece of the understudied auteur, contributes to this scholarship by showing us two modes of time experience: depressive time and narrative time. In the light of Paul Ricoeur’s, Matthew Ratcliffe’s, and Thomas Fuchs’s phenomenologies of time, I will show how the film delineates the phenomenological contours of depressive time and narrative time with the protagonist poet Alexandros’s last day sojourn in the world on the one hand and a series of his time travels on the other. Overall, I frame this new phenomenology of time with Angelopoulos’s cinematic thinking on home. I argue that depressive time underlies the time experience of homelessness while narrative time reorients us towards homecoming. Hence, Eternity and a Day not only contributes to the phenomenology of time but also constitutes an existential philosophy that addresses and redresses what Georg Lukács calls “transcendental homelessness”, the fundamental alienation of modern humanity.